Böhmes Morgen-Röte und Andreaes Chymische Hochzeit - Virginie Pektas (Recherches Germaniques)
Böhme and Andreae are considered as two leading figures of German thought of the seventeenth century: Böhme, because the extent of his theosophical and pansophic vision of the universe changed European philosophy and theology; Andreae, because his Chymical Wedding—all together with the Fama and Confessio—inaugurated, whether he intended it or not, an esoteric movement in which a century torn by sectarian strife and the last gasps of the Holy Roman empire found its expression. Thus the temptation is great to find an affinity between the two authors: accordingly they are regularly mentioned together, in the same breath, in the same sentence, without however the mention going beyond mere juxtaposition. This paper intends to clarify the possible links, both historical and philosophical, uniting the two thinkers, but also their dissonance. It will highlight the fundamental dimension of alchemy understood as spirituality in the work of the two authors.